A glaciogenic sequence from the Early Pleistocene of the Central North Sea. (26th July 2016) - Buckley, Francis Andrew
ABSTRACT: A depositional sequence bounded by upper and lower erosion surfaces covering a 35‐km × 20‐km area within the northern embayment of the Early Pleistocene Central North Sea is dated close to the Jaramillo Normal sub‐chron at approximately 1.0–1.1 Ma. The basal surface cuts shallow marine clays of the upper Nordland Group and is characterized by furrow incisions, mega‐scale glacial lineation textures and bedforms that are all orientated NNW–SSE. The sequence comprises a suite of distinctive bedforms, including a chaotic deposit up to 60 m thick, a series of moulded and lineated depositional bodies and some more complex bedforms, with lithologies shown by petrophysical data to be dominated by overconsolidated clays and thin sand layers. This sequence is considered to represent deposition from the advance and subsequent decay of a marine‐terminating ice‐sheet. The upper surface of the sequence coincides with the so‐called 'Crenulate Reflection' and is characterized by a fluvial channel system, representing final retreat of the ice‐sheet, which was followed by shallow marine conditions and deposition of the Aberdeen Ground Formation. It is considered that the Aberdeen Ground Formation comprises at least two main sequences spanning the Early to Middle Pleistocene.